ANALISIS CONTINUOUS IMPROVEMENT PADA BUDAYA MUTU MADRASAH DI KABUPATEN BANYUWANGI - Fauzi, Muhammad Irfan; Aimah, Siti; Imam Khaudli, Muhammad (JURNAL TARBIYAH, 2024)
Management of learning values, as is known as TQM, is a procedure for continuously strengthening performance at every level of operation or process in every functional zone in a particular organization with a broad background, namely the use of human resources and a lot of existing capital. Meanwhile, "Ross and William Mantja" define TQM as the unification of functions and processes in an organizational framework in order to obtain optimal value in terms of quality of goods and income from sustainable products and services. This received a breath of fresh air with the existence of Law No. 20 of 2003, concerning the national education system. Government regulations and other laws recognize that madrasas are public schools with Islamic characteristics.Referring to the explanation above, seeing the very importance of quality management in educational institutions, and the very importance of making continuous improvements (Continuous Improvement) in Quality Culture, the researcher wants to carry out research with the title "Analysis of Continuous Improvement in Madrasah Quality Culture in Banyuwangi Regency." This research is in the form of a qualitative descriptive study seen from an educational perspective using interview, observation and documentation data collection instruments. It is called qualitative because the nature of the data collected is analyzed qualitatively, not quantitatively using certain measuring instruments.Continuous Improvement or continuous system improvement is one of the ten main elements in TQM. Every product and/or service is produced by utilizing certain processes in a system.